Attraction or differentiation: diachronic changes in the causative alternation of Chinese change of state verbs - Du Jing; Zuo Shan; Li Fuyin Thomas (Cognitive Linguistics)
This study examines the interplay of attraction and differentiation through the diachronic encoding of causative alternations in Chinese. A corpus-based analysis is conducted to profile the use of two Change of State verbs (COS verbs), pò ‘break’ and kāi ‘open’, focusing on their argument structure constructions. The analysis yields two main insights: (i) In Chinese, there are four pairs of causative alternations. The first pair, CA1, involving the alternation between NP1+COS+NP2 and NP2+COS, serves as the source for two diachronic trajectories. In the first trajectory, NP1+COS+NP2 is replaced by NP1+V+COS+NP2, and forms CA2 with NP2+COS. Subsequently, NP2+COS transitions into NP2+V+COS, and constitutes CA3 with NP1+V+COS+NP2. In the second trajectory, NP1+COS+V+NP2 and NP2+COS+V emerge and form CA4. (ii) Evidence of attraction is found in the mutual influence between the causative variants NP1+V+COS+NP2 and NP1+COS+V+NP2, and in the modeling effect of the causative variant NP1+V+COS+NP2 on the inchoative variant NP2+V+COS. Differentiation is supported by the anchoring force of a larger constructional network, including the transitive/intransitive opposition and compound constructions. This study advances the theoretical understanding of the intertwinement of attraction and differentiation by elucidating the diachronic evolution of causative alternations in Chinese.